TINJAUAN YURIDIS PELAKSANAAN PERIZINAN PEMBUANGAN LIMBAH MEDIS RUMAH SAKIT X BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Jason Herodion Thomas; Demson Tiopan (LPPM Universitas Ekasakti Padang, 2023)
Environmental Quality Standard (environment quality standard) is intended to provide direction and guidance on environmental management in an effort to prevent and identify environmental pollution. Environmental quality and the quality of waste that has been allowed to be disposed of in environmental media can be observed thanks to the Environmental Quality Standard. Therefore, pollution and environmental damage are considered to have occurred if the quality of the environment exceeds the limits of environmental quality standards. The purpose of this study is to find out how medical waste management must be carried out based on the Regulation of the Minister of Environment. Implementation of waste disposal permits according to the Environmental Law and knowing how the law enforcement process against parties who dispose of medical waste without permits according to the Law. In this study using Normative juridical research methods. In managing the environment is based on principles related to environmental management. The provisions governing Environmental Protection and Management in the Law explain that the environment must be protected and managed properly in accordance with the principles of justice, sustainability, and state responsibility. Environmental Management Protection Permits and environmental permits are prerequisites for any business that produces medical waste. This medical waste poses a threat to society and the environment due to its nature. Thus, managing medical waste must be done through the precautionary principle by applying licensing instruments that must be properly regulated.